Fatalisme dan Kemiskinan Komunitas Nelayan: Fatalism and Poverty in Fishing Communities - Maksud Hakim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
This study aims to reveal the fatalistic work culture process as a cause of poverty for fishermen. As part of an urgent cultural aspect, Fatalism has been an inseparable part of their social life. Fatalism is an attitude that has been a stronghold for a long time and becomes a habit. In this case, the most important thing to express is the belief or trust of fishermen related to the coastal environment. This research took place on the southern coast of the Sulawesi Island, in Pandang-Pandang village, Arungkeke District, Jeneponto Regency, South Sulawesi Province, Indonesia. The informants were 5 poor fishermen from the Sawi (fishing boat crew) who were interviewed in-depth and conducted observation of the surrounding environment. To strengthen research data, Literature studies, interview and observation results were also conducted. Data analysis used three path techniques including data reduction, categorization, and conclusion drawing. This research shows that; (1) The fatalistic attitude of the fishing community of Pandang-Pandang village manifested in the belief that life has been determined by God while humans only live and accept it, (2) Weak instrumental values ??of the fishing community in the form of not overly pursuing more values ??at work. Both of these are fatalistic attitudes. The conclusion of this research is the emergence of a fatalistic attitude in the fishing community is the result of their appreciation of God, Nature, Humans, and Life. This appreciation has been going on for a long time so that it is manifested in the form of an attitude of life than becoming an actor.